Dressing plasmon resonance with particle-microcavity architecture for efficient nano-optical trapping and sensing - Zhang, Haixi (2014)
We propose a particle-microcavity scheme for efficient optical trapping and sensing. When a resonant plasmonic nanoparticle (NP) is placed inside a microcavity with high Q-factor, sensitivity is enhanced in the far-field extinction while near-field around the NP is barely affected. Stable near-field and high sensitivity for optical trapping and ultrasensitive detection of nanosized targets are therefore realized simultaneously. Such a particle-microcavity system opens up a new hybrid nanophotonic device platform that combines the unique merits of conventional and plasmonic integrated photonics.